Scutellarin Suppresses NLRP3 Inflammasome Activation in Macrophages and Protects Mice against Bacterial Sepsis - Liu, Yi; Jing, Yan-Yun; Zeng, Chen-Ying; Li, Chen-Guang; Xu, Li-Hui; Yan, Liang; Bai, Wen-Jing; Zha, Qing-Bing; Ouyang, Dong-Yun; He, Xian-Hui (Frontiers in Pharmacology, 2018)
The NLRP3 inflammasome plays a critical role in mediating the innate immune defense against pathogenic infections, but aberrant activation of NLRP3 inflammasome has been linked to a variety of inflammatory diseases. Thus targeting the NLRP3 inflammasome represents a promising therapeutic for the treatment of such diseases. Scutellarin is a flavonoid isolated from Erigeron breviscapus (Vant.) Hand.-Mazz. and has been reported to exhibit potent anti-inflammatory activities, but the underlying mechanism is only partly understood. In this study, we aimed to investigate whether scutellarin could affect the activation of NLRP3 inflammasome in macrophages. The results showed that scutellarin dose-dependently reduced caspase-1 activation and decreased mature interleukin-1β (IL-1β) release in lipopolysaccharide (LPS)-primed macrophages upon ATP or nigericin stimulation, indicating that scutellarin inhibited NLRP3 inflammasome activation in macrophages. Consistent with this, scutellarin also suppressed pyroptotic cell death in LPS-primed macrophages treated with ATP or nigericin. ATP or nigericin-induced ASC speck formation and its oligomerization were blocked by scutellarin pre-treatment. Intriguingly, scutellarin augmented PKA-specific phosphorylation of NLRP3 in LPS-primed macrophages, which was completely blocked by selective PKA inhibitor H89, suggesting that PKA signaling had been involved in the action of scutellarin to suppress NLRP3 inflammasome activation. Supporting this, the inhibitory effect of scutellarin on NLRP3 inflammasome activation was completely counteracted by H89 or adenyl cyclase inhibitor MDL12330A. As NLRP3-dependent release of IL-1β has a critical role in sepsis, the in vivo activity of scutellarin was assayed in a mouse model of bacterial sepsis, which was established by intraperitoneally injection of a lethal dose of viable Escherichia coli. Oral administration of scutellarin significantly improved the survival of mice with bacterial sepsis. In line with this, scutellarin treatment significantly reduced serum IL-1β levels and attenuated the infiltration of inflammatory cells in the liver of E. coli-infected mice. These data indicated that scutellarin suppressed NLRP3 inflammasome activation in macrophages by augmenting PKA signaling, highlighting its potential therapeutic application for treating NLRP3-related inflammatory diseases.